2011
DOI: 10.1093/jjco/hyr117
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABCB1, 5-HT3B Receptor and CYP2D6 Genetic Polymorphisms with Ondansetron and Metoclopramide Antiemetic Response in Indonesian Cancer Patients Treated with Highly Emetogenic Chemotherapy

Abstract: Objective: Suboptimal treatment of chemotherapy-induced nausea and vomiting and unsatisfactory response to antiemetic drugs cause impairment of cancer patient's daily functioning. This study was aimed to investigate the association of selected germline polymorphisms with ondansetron and metoclopramide response in Indonesian cancer patients treated with highly emetogenic chemotherapy. Methods: We enrolled 202 chemotherapy naïve patients treated with cisplatin at a dosage of !50 mg/m 2 as monotherapy or as combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 33 publications
(46 reference statements)
0
61
1
Order By: Relevance
“…Furthermore, an in vitro cell culture study revealed that this deletion increased the activity of the promoter of the HTR3B gene [32]. Serotonin receptor type 3 HTR3B rs45460698 -100_-102delAAG [31,32] rs1176744 Y129S [33] HTR3C rs6807362 A405G [33] rs6766410 K163N [33] HTR3D rs6443930 G36A [34] Serotonin transporter SLC22A1 rs12208357 R61C [35] rs55918055 C88R [35] rs34130495 G401S [35] rs35167514 M420del [35] rs34059508 G465R [35] ABCB1 rs1045642 Synonymous [36][37][38] rs2032582 S893T [37,38] rs1128503 Synonymous [37] Metabolizing enzyme for serotonin receptor antagonists…”
Section: -Ht 3 Receptor Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an in vitro cell culture study revealed that this deletion increased the activity of the promoter of the HTR3B gene [32]. Serotonin receptor type 3 HTR3B rs45460698 -100_-102delAAG [31,32] rs1176744 Y129S [33] HTR3C rs6807362 A405G [33] rs6766410 K163N [33] HTR3D rs6443930 G36A [34] Serotonin transporter SLC22A1 rs12208357 R61C [35] rs55918055 C88R [35] rs34130495 G401S [35] rs35167514 M420del [35] rs34059508 G465R [35] ABCB1 rs1045642 Synonymous [36][37][38] rs2032582 S893T [37,38] rs1128503 Synonymous [37] Metabolizing enzyme for serotonin receptor antagonists…”
Section: -Ht 3 Receptor Genesmentioning
confidence: 99%
“…Altered function of this transporter, by the investigated SNP, may be different among different ethnicities or races. Perwitasari et al analyzed the association of nine SNPs, in the HTR3B, ABCB1 and CYP2D6 genes, with CINV in 202 cancer patients [37]. Although SNPs of the HTR3B and CYP2D6 genes were not associated with CINV, the CTG haplotype, constructed from three SNPs of the ABCB1 gene (i.e., rs1045642, rs2032582, rs1128503), increased intensity of the delayed CINV (p = 0.02).…”
Section: -Ht 3 Receptor Antagonist Transporter Genesmentioning
confidence: 99%
“…14,15 Moreover, there are several reports showing that polymorphisms of the adenosine triphosphate-binding cassette subfamily B member 1 (ABCB1) transporter protein are also associated with CINV and postoperative nausea and vomiting. [16][17][18][19][20] However, these investigations were on the basis of first-generation 5-HT 3 receptor antagonists, such as ondansetron and granisetron, without neurokinin-1 receptor antagonist, and there are conflicting reports on the effects of ABCB1 polymorphisms. Furthermore, in these studies, the use of antiemetic medications, such as dexamethasone, was not in accordance with the antiemetic guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Even some previous studies did not show the consistency about the significancy of statistical results, however the pattern of the genotypes and the patients' response were similar. [6][7][8][9][10] One of the previous study supported that the polimorphism of CYP2D6 resulted the significant difference of tropisetron serum concentration in poor metabolizer, extensive metabolizer and ultra-rapid metabolizer. 8 This study is aimed to evaluate the association between ondansetron serum concentration and the antiemetic responses, polymorphisms of 5HT3B receptor, CYP2D6 and ABCB1 genes in Indonesian cancer patients treated with high emetogenic cytostatics.…”
Section: Introductionmentioning
confidence: 82%
“…The patients were excluded if nausea or vomiting were present 24 hours before chemotherapy; the use of other antiemetics such as benzodiazepines or neuroleptics, radiotherapy within 24 hours before start of chemotherapy, use of opioids within the last 2 weeks, use of inducers of CYP3A4 or inhibitors of CYP2D6, patients with concomitant diseases that might cause nausea or vomiting, patients with AST-ALT > 2,5 x ULN for patients without liver metastases > 5 x ULN for patients with liver metastases, renal dysfunction defined by creatinine clearance < 60 ml/minute, brain metastases and patients with artificial stoma or pregnancy. 8,9 We did the informed consent to all of the patients before the recruitment. This study has been approved by The Medical and Health Research Ethics Committee of the Faculty of Medicine, Universitas Gadjah Mada, Yogyakarta, Indonesia.…”
Section: Patientsmentioning
confidence: 99%